The adaptive significance of geophagy for japanese macaques (Macaca fuscata) at Arashiyama, Japan - Wakibara, James V.; Wink, Michael (International journal of primatology, 2001)
We gathered data on the amount, composition, and rate of ingestion of foods and soils by the provisioned Japanese macaques (Macaca fuscata fuscata) at Arashiyama, Japan. Behavioral observations spanned one year on 8 adult females, using focal animal sampling. We analyzed a subsample of their foods for nutritional and toxic secondary compound content. We also analyzed soils eaten by the macaques for several physical-chemical properties and tested their adsorption affinity to tannins and alkaloids. Geophagy occurred at a high rate of 2.97 g/indiv./day with an elevated frequency in the afternoon. About two-thirds of their foods (by fresh weight) were provisioned items, which are extremely rich in proteins and soluble carbohydrates. The soils that they ingested were generally poor in mineral elements, the bio-availability of which was low. The soils had a high adsorption capacity for plant alkaloids but were poorly absorptive for tannins. They were rich in clay minerals of proven buffering capacity. Geophagy at Arashiyama may improve the health of macaques via buffering gastric upset. We discuss the results from the viewpoint of several hypotheses on geophagy.